H.D.’s War Ghosts - Bérengère Riou (Caliban: French Journal of English Studies)
Against the typical postwar understanding of occultism as apolitical and escapist, this article showcases a striking instance of “engaged occultism” in the modernist poet H.D. [Hilda Doolittle]. By focusing on the poet’s spiritualist experiments during World War Two, notably her communications with what she believed to be the spirits of dead R.A.F. airmen, it demonstrates the fusion of political thought and occultist thought in her war writings. It brings together studies of the modernist occult and studies of war modernism to analyze the complex, sometimes self-contradictory belief system of H.D., its relationship to empire and race, and its formal implications in both poetry (Trilogy) and prose (Majic Ring and Within the Walls).